Kenn Nesbitt’s Ideas through His Poem “Sleeping Beauty” - Syafrizal Syafrizal; Raden Rara Evi Oktaviani Sandhi (English Language in Focus (ELIF), 2022)
The title of this research is Kenn Nesbitt’s Ideas through His Poem “Sleeping Beauty”. The theoretical approach uses the expressive approach by Abrams and the method applied is the qualitative method. The instruments of this research are to observe, collect, and analyze the data with the lines from the poem Sleeping Beauty. The results shows that Nesbitt writes Sleeping Beauty in an imaginable yet humorous way to represent his ideas about what children mostly want to know about a story of a fairy tale. At the end of the lines in the poem, Nesbitt delivers a realistic and funny passage for little children that are in contrast and different from their imaginations.